DNA methylation clock DNAmFitAge shows regular exercise is associated with slower aging and systemic adaptation - Matyas Jokai; Ferenc Torma; Kristen M. McGreevy; Erika Koltai; Zoltan Bori; Gergely Babszki; Peter Bakonyi; Zoltan Gombos; Bernadett Gyorgy; Dora Aczel; Laszlo Toth; Peter Osvath; et al. (GeroScience, 2023)
DNAmPhenoAge, DNAmGrimAge, and the newly developed DNAmFitAge are DNA methylation (DNAm)-based biomarkers that reflect the individual aging process. Here, we examine the relationship between physical fitness and DNAm-based biomarkers in adults aged 33–88 with a wide range of physical fitness (including athletes with long-term training history). Higher levels of VO 2 max ( ρ = 0.2, p = 6.4E − 4, r = 0.19, p = 1.2E − 3), Jumpmax ( p = 0.11, p = 5.5E − 2, r = 0.13, p = 2.8E − 2), Gripmax ( ρ = 0.17, p = 3.5E − 3, r = 0.16, p = 5.6E − 3), and HDL levels ( ρ = 0.18, p = 1.95E − 3, r = 0.19, p = 1.1E − 3) are associated with better verbal short-term memory. In addition, verbal short-term memory is associated with decelerated aging assessed with the new DNAm biomarker FitAgeAcceleration ( ρ : − 0.18, p = 0.0017). DNAmFitAge can distinguish high-fitness individuals from low/medium-fitness individuals better than existing DNAm biomarkers and estimates a younger biological age in the high-fit males and females (1.5 and 2.0 years younger, respectively). Our research shows that regular physical exercise contributes to observable physiological and methylation differences which are beneficial to the aging process. DNAmFitAge has now emerged as a new biological marker of quality of life.

Nectar- and stigma exudate-specific expression of an acidic chitinase could partially protect certain apple cultivars against fire blight disease - Anita Kurilla; Timea Toth; Laszlo Dorgai; Zsuzsanna Darula; Tamas Lakatos; Daniel Silhavy; Zoltan Kerenyi; Geza Dallmann (Planta, 2020)
Main conclusion Certain apple cultivars accumulate to high levels in their nectar and stigma exudate an acidic chitinase III protein that can protect against pathogens including fire blight disease causing Erwinia amylovora. Abstract To prevent microbial infections, flower nectars and stigma exudates contain various antimicrobial compounds. Erwinia amylovora , the causing bacterium of the devastating fire blight apple disease, is the model pathogen that multiplies in flower secretions and infects through the nectaries. Although Erwinia -resistant apples are not available, certain cultivars are tolerant. It was reported that in flower infection assay, the ‘Freedom’ cultivar was Erwinia tolerant, while the ‘Jonagold’ cultivar was susceptible. We hypothesized that differences in the nectar protein compositions lead to different susceptibility. Indeed, we found that an acidic chitinase III protein (Machi3-1) selectively accumulates to very high levels in the nectar and the stigma exudate of the ‘Freedom’ cultivar. We show that three different Machi3 - 1 alleles exist in apple cultivars and that only the 5B - Machi3 - 1 allele expresses the Machi3-1 protein in the nectar and the stigma exudate. We demonstrate that the 5B - Machi3 - 1 allele was introgressed from the Malus floribunda 821 clone into different apple cultivars including the ‘Freedom’. Our data suggest that MYB-binding site containing repeats of the 5B- Machi3 - 1 promoter is responsible for the strong nectar- and stigma exudate-specific expression. As we found that in vitro, the Machi3-1 protein impairs growth and biofilm formation of Erwinia at physiological concentration, we propose that the Machi3-1 protein could partially protect 5B - Machi3 - 1 allele containing cultivars against Erwinia by inhibiting the multiplication and biofilm formation of the pathogen in the stigma exudate and in the nectar.

PACAP Is Protective in a Rat Model of Retinopathy of Prematurity - Timea Kvarik; Barbara Mammel; Dora Reglodi; Krisztina Kovacs; Dora Werling; Brigitta Bede; Alexandra Vaczy; Eszter Fabian; Gabor Toth; Peter Kiss; Andrea Tamas; Tibor Ertl; et al. (Journal of Molecular Neuroscience, 2016)

The novel panel assay to define tumor-associated antigen-binding antibodies in patients with metastatic melanomas may have diagnostic value - Beatrix Kotlan; Gabriella Liszkay; Miri Blank; Orsolya Csuka; Timea Balatoni; Laszlo Toth; Klara Eles; Szabolcs Horvath; Gyorgy Naszados; Judit Olasz; Balazs Banky; Jozsef Toth; et al. (Immunologic Research, 2015)